5 - La contribution des jeunes à l’alternance politique au Sénégal : Le rôle de Bul faale et de Y’en a marre - Moda Dieng (African Sociological Review, 2015)
This paper is a contribution to the research on the role of youth in the democratization process in Africa. More precisely, its analysis is confined to the influence of Bul Faale and Y’en a marre in political changes that occurred in Senegal, both in 2000 and in 2012. Always originating from hip-hop, these two movements have been at the forefront of mobilizations that sparked changes in the ruling majority. Interestingly, this contrasts with the situation of political and economic marginalization the youth continues to struggle with